A computational study on porosity evolution in parts produced by selective laser melting - Tan, Jie Lun (2019)
Selective laser melting (SLM) is a powder-bed additive manufacturing process that uses laser to melt powders, layer by layer to generate a functional 3D part. There are many different parameters, such as laser power, scanning speed, and layer thickness, which play a role in determining the quality of the printed part. These parameters contribute to the energy density applied on the powder bed. Defects arise when insufficient or excess energy density is applied. A common defect in these cases is the presence of porosity. This paper studies the formation of porosities when inappropriate energy densities are used. A computational model was developed to simulate the melting and solidification process of SS316L powders in the SLM process. Three different sets of process parameters were used to produce 800-µm-long melt tracks, and the characteristics of the porosities were analyzed. It was found that when low energy density parameters were used, the pores were found to be irregular in shapes and were located near the top surface of the powder bed. However, when high energy density parameters were used, the pores were either elliptical or spherical in shapes and were usually located near the bottom of the keyholes.